Measuring pulmonary oxygen uptake kinetics: Contemporary perspectives - Rossiter, H. B.; Poole, D. C. (Experimental Physiology, 2024)
As championed by Brian J. Whipp, resolution of pulmonary oxygen uptake (VO2) kinetics following exercise onset provides a unique and non-invasive window into muscle energetics, mitochondrial function and the mechanistic bases for exercise tolerance (reviewed by Poole & Jones, 2012; Rossiter, 2011). In theory and practice, beyond that time taken for blood transit from the exercising muscles to reach the lungs (i.e., phase I), the close-to-exponential so-called `primary` or `fundamental` VO2 response (i.e., phase II) at the blood-gas barrier in the lung closely reflects that across the exercising muscles (reviewed by Poole & Jones, 2012; Rossiter, 2011).